Abortion, euthanasia and organ transplantation. An orthodox canonical point of view (BioLaw Journal - Rivista di BioDiritto, 2023)
The Orthodox Church constantly preserves and promotes its teaching of faith and its canonical discipline concerning human life, health and care of them, being at the same time attentive and open to new medical discoveries that can help man in his journey to the eternal Creator. Therefore, the Orthodox Church condemns any act by which human life is endangered or destroyed, as well as all those involved in such actions, considering them inconsistent with its teaching of faith and its own canonical discipline. For questions relating to abortion, euthanasia and organ transplantation, the canonical point of view is known and promoted by all the autocephalous Orthodox Churches, which seek to insert the fundamental principles relating to these into state legislation through their own missionary pastoral activity of faith on life, on the human person and on his relationship with God and with his fellow men, as well as on health understood as a gift from God. With regard to organ transplantation, the Orthodox Church shows an openness to this medical practice, but circumscribes it in the spirit of Christian love and the promotion and the defense of the dignity of the human person.
Keywords: Abortion; euthanasia; organ transplantation; orthodox theology; orthodox bioethics